Cyclodextrin Inclusion Complexes of Auranofin and Its Iodido Analog: A Chemical and Biological Study - Damiano Cirri; Ida Landini; Lara Massai; Enrico Mini; Francesca Maestrelli; Luigi Messori (MDPI AG, 2021)
Auranofin (AF) and its iodido analog, i.e., Au(PEt3) I (AFI), were reported to exhibit very promising anticancer properties both in vitro and in vivo. However, both these gold compounds have a scarce aqueous solubility that hampers their pharmaceutical use. Here, we explore whether encapsulation of these metallodrugs inside hydroxypropyl-beta-cyclodextrin (HPβ-CD) may lead to an improved biopharmaceutical profile for the resulting adducts. Phase solubility studies, performed at 25 °C in an aqueous buffer, revealed, in both cases, the formation of a 1:1 drug to cyclodextrin complex; a far greater apparent stability constant (K1:1) was measured for AFI compared to AF (331 M−1 versus ca. 30 M−1). NMR studies conducted on the AFI/HPβ-CD system confirmed the formation of a stable 1:1 adduct. Then, binary systems of AF and AFI with HPβ-CD were prepared by colyophilization and characterized by DSC and PXRD. The results revealed the occurrence of drug complexation and/or amorphization for the AFI/HPβ-CD binary system. Afterwards, the antiproliferative properties of the two cyclodextrin adducts and of the corresponding free drugs were comparatively evaluated in vitro in three representative ovarian cancer cell lines, i.e., A2780, SKOV3, and IGROV-1. The results, in all cases, point out that CD complexation of the two gold drugs does not substantially affect their biological activity. The implications of these findings are discussed in the frame of the current knowledge of AF and its analogs.